2002
DOI: 10.1002/app.10940
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis of polyethylene and ethylene vinylacetate copolymer blends irradiated by electron beam

Abstract: Dynamic mechanical properties of nonirradiated and irradiated blends of polyethylene (PE) and ethylene vinylacetate (EVA) copolymer have been determined. Effect of addition of EVA and radiational crosslinking on loss and storage modulus, tan ␦, and transition temperatures were determined. Increase in transition temperatures on exposure to radiation and decrease in transition temperatures with addition of EVA is observed. Peak broadening is observed on exposure to radiation. Values of the storage modulus increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…and Sethi et al . showed that amorphous thermal transitions in this temperature range were that of β transitions . When the log of each storage modulus was plotted on the Y ‐axis, the β transitions were more easily seen.…”
Section: Resultsmentioning
confidence: 93%
“…and Sethi et al . showed that amorphous thermal transitions in this temperature range were that of β transitions . When the log of each storage modulus was plotted on the Y ‐axis, the β transitions were more easily seen.…”
Section: Resultsmentioning
confidence: 93%
“…20 Sethi et al have investigated the dynamic mechanical properties of nonirradiated and irradiated blends of low-density polyethylene and ethylene vinyl acetate copolymer blends. 21 They have observed an increase in the glass transition temperatures on exposure to radiation and decrease in the glass transition temperature with addition of EVA. Martinez-Salazar et al studied the rheological properties of metallocene-catalyzed linear polyethylenes and those of blends prepared with ethylene vinyl acetate copolymer.…”
mentioning
confidence: 97%
“…Radiation is a very convenient method to modify the properties of polymeric materials by cross‐linking, grafting, and degradation [7–9]. The molecular changes, induced by radiation, in a polymer may be classified as main‐chain bond scission and cross‐linking.…”
Section: Introductionmentioning
confidence: 99%